Phenotypic characterization of the desi (local) cattle reared by the tribal communities of Wayanad district, Kerala, South India - PREM, A; SANKAR, R; ZACHARIAH, A; DINESH, C N; ROJAN, P M (The Indian Journal of Animal Sciences, 2023)
This study pertained to the phenotypic characterization of Wayanad desi cattle, a lesser-known indigenous cattle population reared mainly in the tribal hamlets of Wayanad district, Kerala, South India. Information on the habitat, status, management, utility and performance of the cattle and data on the morphological and morphometric traits were recorded using the ICAR-NBAGR guidelines with modifications. The main breeding tract of Wayanad desi cattle was in Thavinhal, Thondernad, Ambalavayal and Noolpuzha panchayaths of Wayanad district. These animals were reared under an extensive system of management and a loose house system in simple kachcha housing. They are low milk producers and the average daily yield was just above one litre. These animals weresmall in size, predominantly solid brown in colour, with a straight forehead and face. These desi cattle share several qualitative and quantitative features with other varieties of cattle in Kerala, eventhough their geographic distribution was different.